2021
DOI: 10.3996/jfwm-20-040
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Freshwater Invertebrates in Alpine Lakes and Streams Following Eradication of Nonnative Trout with Rotenone

Abstract: Nonnative fish eradication via the piscicide rotenone is an effective tool for fisheries management and conservation of native species. However, the long-term effects on non-target organisms, including benthic invertebrates and zooplankton in alpine lakes, are under-studied and are poorly understood. As part of a landscape-scale native fish conservation project, we assessed the effects of 50 ppb rotenone on the aquatic invertebrate community by comparing pre- and post-rotenone treatment density and diversity m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Previous research of rotenone impacts on freshwater invertebrate communities has indicated that gill-breathing insect larvae (e.g., Trichoptera and Plecoptera) are typically eliminated first and replaced by more tolerant taxa such as chironomids and occasionally by amphipods (Mangum and Madrigal, 1999;Beaulieu et al, 2021;Schnee et al, 2021). Correspondingly, our CCA results showed declines in EPT taxa and an increased abundance of chironomids and amphipods in the treated lakes (Fig.…”
Section: Rotenone Impacts On Community Compositionsupporting
confidence: 72%
“…Previous research of rotenone impacts on freshwater invertebrate communities has indicated that gill-breathing insect larvae (e.g., Trichoptera and Plecoptera) are typically eliminated first and replaced by more tolerant taxa such as chironomids and occasionally by amphipods (Mangum and Madrigal, 1999;Beaulieu et al, 2021;Schnee et al, 2021). Correspondingly, our CCA results showed declines in EPT taxa and an increased abundance of chironomids and amphipods in the treated lakes (Fig.…”
Section: Rotenone Impacts On Community Compositionsupporting
confidence: 72%